From Austen to social Darwinism: changing ethics - Hooper, KC; Xu, G (New Zealand Institute of Chartered Accountants, 2010)
In 1927, the New Zealand Society of Accountants adopted its first guide on professional ethics. The short document was so full of gentlemanly notions that it could have been written by Jane Austen and came at a time when the accounting bodies in the Dominions were lobbying for the privileged title of “chartered”. The term was then held officially only by the English and Scottish branches of the profession. Since then there has been a major shift in ethical emphasis. The 2003 Code of Ethics (COE) can be viewed as a shift from Kant to social Darwinism via utilitarianism, but also a shift from a focus on the character of an accountant to the character of accounting. The first paragraph in Professional Ethics 1927 reads: “Every member of the Society in the practice of his profession or in the course of his service to his employer should give such service with absolute fidelity and should be actuated by a spirit of fairness to client and employer, considerate to the fellow practitioners, loyalty to his country, and devotion to high ideals of courtesy and honour.”